2012
DOI: 10.1200/jco.2011.36.4109
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Inflammation, and ω-3 and ω-6 Fatty Acid Intake Among Breast Cancer Survivors

Abstract: PurposeEvidence suggests that inflammation may drive fatigue in cancer survivors. Research in healthy populations has shown reduced inflammation with higher dietary intake of ω-3 polyunsaturated fatty acids (PUFAs), which could potentially reduce fatigue. This study investigated fatigue, inflammation, and intake of ω-3 and ω-6 PUFAs among breast cancer survivors.MethodsSix hundred thirty-three survivors (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 55 publications
8
88
1
Order By: Relevance
“…This finding supported the results of a case study by the same group [270], which noted structural changes in the brain of a patient with chronic fatigue syndrome detected by NMR spectroscopy following a course of EPA supplementation [270]. There is also robust evidence demonstrating that EPA supplementation produces clinically significant reductions in the levels of severe intractable fatigue experienced by sufferers of cancer [271,272].…”
Section: Lipid Rafts Mlrs and N-3 Pufas In Chronic Fatigue Syndromesupporting
confidence: 74%
“…This finding supported the results of a case study by the same group [270], which noted structural changes in the brain of a patient with chronic fatigue syndrome detected by NMR spectroscopy following a course of EPA supplementation [270]. There is also robust evidence demonstrating that EPA supplementation produces clinically significant reductions in the levels of severe intractable fatigue experienced by sufferers of cancer [271,272].…”
Section: Lipid Rafts Mlrs and N-3 Pufas In Chronic Fatigue Syndromesupporting
confidence: 74%
“…We focused on two inflammatory markers, IL-6 and CRP, which have been associated with cancer-related fatigue (Schubert et al, 2007; Alfano et al, 2012) and with HRV (Sajadieh et al, 2004; Sloan et al, 2007). Plasma levels of IL-6 were determined by the Quantikine high-sensitivity ELISA kit (R&D Systems, Minneapolis, MN), with a lower detection limit of 0.039 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome of this randomized controlled trial was fatigue, and results showed improvements in fatigue and energy among women assigned to the yoga group relative to women assigned to the health education control condition (Bower et al, 2012). In addition to behavioral outcomes, the trial was designed to examine effects on inflammatory processes, which may underlie symptoms of cancer-related fatigue (Bower et al, 2002; Collado-Hidalgo et al, 2006; Orre et al, 2011; Bower et al, 2011b; Alfano et al, 2012). Based on preliminary work suggesting beneficial effects of yoga on inflammation (Pullen et al, 2008; Pullen et al, 2010), we hypothesized that women randomly assigned to the targeted Iyengar yoga intervention would show decreases in markers of inflammatory activity relative to health education controls.…”
Section: Introductionmentioning
confidence: 99%